2020
DOI: 10.1007/s10555-020-09920-8
|View full text |Cite
|
Sign up to set email alerts
|

Splice variants of RAS—translational significance

Abstract: One of the mechanisms potentially explaining the discrepancy between the number of human genes and the functional complexity of organisms is generating alternative splice variants, an attribute of the vast majority of multi-exon genes. Members of the RAS family, such as NRAS, KRAS and HRAS, all of which are of significant importance in cancer biology, are no exception. The structural and functional differences of these splice variants, particularly if they contain the canonical (and therefore routinely targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…At the same time, KRAS4B will only be given the farnesyl radical. 27 , 28 These are critical differences with great importance regarding targeted therapy.…”
Section: Krasmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, KRAS4B will only be given the farnesyl radical. 27 , 28 These are critical differences with great importance regarding targeted therapy.…”
Section: Krasmentioning
confidence: 99%
“…Using genetic engineering techniques like CRIPS/Cas and TALEN, 74 the endogenous TCR can be silenced, and then, transduction of a new laboratory-designed TCR construct can be done for another expression on T-cells and induction of a specific response against cells presenting certain HLA-epitope complexes derived from KRAS-mutant variants. 75 …”
Section: Krasmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of Ras isoform expression during development by real-time polymerase chain reaction (PCR) in mouse tissues indicated a relative contribution of KRas4B > > NRas ≥ KRas4A > HRas to total Ras expression (Newlaczyl et al 2017 ), where KRas4B is about 60–99% of all Ras transcripts. Recent data have also suggested that spliced variants are translationally significant (Raso 2020 ). This may reflect the dependence of multiple factors, including cell type, tissue heterogeneity, timing, sparsity of data, defining flexible statistical frameworks for complex differential patterns in gene expression, assigning a reference, errors and missing data, and from our standpoint as we discuss here, key factors are measuring chromatin accessibility (Buenrostro et al 2015 ; Cusanovich et al 2015 ) and epigenetics, such as DNA methylation (Karemaker and Vermeulen 2018 ) and more (Lahnemann et al 2020 ).…”
Section: Differential Ras Isoform Expressionmentioning
confidence: 99%
“…Small GTPases contain a diverse set of exons with propensity for alternative splicing that can impact biology, including neurodevelopmental disorders and cancer ( Lee et al, 2022 ). Within cancer, splicing changes in small GTPases have been noted for genes including NRAS , KRAS , HRAS , and RAC1 ( Rásó, 2020 ). The Neuroblastoma RAS ( NRAS ) gene has five expressed isoforms, with two of the isoforms elevated in melanoma patients ( Duggan et al, 2019 ; Yan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%